Small ruminant production in dryland regions of India: Status, challenges and opportunities - KUMAR, ARUN; MISRA, S S; CHAUHAN, I S; GOWANE, G R; SHINDE, A K (The Indian Journal of Animal Sciences, 2021)
Small ruminants are important components of smallholder production systems in dry regions of the country andrequire technological transformation for bringing the farmers out of the vicious cycle of poverty. There is hugescope of improving the income and livelihood of farmers in these harsh topographies because of expanding marketand demand for small ruminant products. Live animal sale is the main source of income from small ruminantscontribute up to three-fourths-of total income. Milk of sheep is produced in negligible amount and consumed inhouseholds while goat milk is well in demand but small portion is sold by farmers and mostly used in households.The price of wool is depressed, whereas carpet wool produced in some regions receives prime price in the market.The main factors affecting small ruminant production in dry areas are feed scarcity, poor genetic make of animals,poor health cover facilities, lack of proximity to market and climate change effects. The technological adoption forenhancing productivity of small ruminants in dry areas has been discussed in this overview. The genetic improvement of small ruminant resources, valuation of breeds, exploring value addition/alternative uses of wool and goat milk, improvement of range management, feed base, use of unconventional feeds, flock health management, reproduction management, improving feed efficiency, value addition, quality issues, creating farmers' organisations, improving market access are some of the issues that need priority in research and development for improving productivity of small ruminants for better livelihood security and income generation of farmers in dryland regions. With the concerted efforts of research, extension and development workers, living conditions of small ruminants farmers can be improved which will alleviate poverty, create employment opportunity in rural areas and reduce migration of younger generation to the cities.